Exchange Rate Arrangements and Currency Convertibility : Developments and Issues - Johnston, R.; Swinburne, Mark. (Washington, D.C. : International Monetary Fund, 1999)
This study reviews the developments and issues in the exchange arrangements and currency convertibility of IMF members. The principal information source for this report is the Annual Report on Exchange Arrangements and Exchange Restrictions prepared in consultation with national authorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet